Organizational routines and sustainability strategizing in the port sector - Aquino-Hübler, Eduardo (2024)
The goal of this research was to comprehend the interrelation between the strategizing process and the constitutive aspects of organizational routines. Employing a qualitative methodology, a case study was conducted at the Port Authority of Valencia. Data collection encompassed interviews, observation, and document analysis. Through the analysis of narratives and pattern matching, a permeable relationship between strategizing and routines was identified, indicating an inseparable amalgamation of their key constituents. The demarcation between the components of strategizing and organizational routines is faint, uncertain, and intertwined within an indivisible process. Conceptualizing organizational routines as a fusion of actors, processes, and strategic content, localized spatially and temporally where reasoning and action intersect contingent upon context, underscores the relevance of approaching strategy as a practice, thereby broadening its scope.